Feasibility of Planting Trees around Buildings as a Nature-Based Solution of Carbon Sequestration—An LCA Approach Using Two Case Studies - Grossi, Felipe (2022)
In response to Canada’s commitment to reducing greenhouse gas emissions and to making pathways to achieve carbon neutral buildings, this paper presents two real case studies. The paper first outlines the potential of trees to absorb CO2 emissions through photosynthesis, and the methods used for the estimation of their annual carbon sequestration rates. The net annual carbon seques tration rate of 0.575 kgCO2eq/m2 of tree cover area is considered in our study. Then, this paper presents the carbon life cycle assessment of an all-electric laboratory at Concordia University and of a single-detached house, both located in Montreal. The life cycle assessment (LCA) calculations were performed using two software tools, One Click LCA and Athena Impact Estimator for Buildings. The results in terms of Global Warming Potential (GWP) over 60 years for the laboratory were found to be 83,521 kgCO2eq using One Click LCA, and 82,666 kgCO2eq using Athena. For the single-detached house that uses natural gas for space heating and domestic hot water, the GWP was found to be 544,907 kgCO2eq using One Click LCA, and 566,856 kgCO2eq using Athena. For the all-electric laboratory, a garden fully covered with representative urban trees could offset around 17% of the total life cycle carbon emissions. For the natural gas-powered single-detached house, the sequestration by trees is around 3% of the total life cycle carbon emission. This paper presents limits for achieving carbon neutral buildings when only the emissions sequestration by trees is applied, and discusses the main findings regarding LCA calculations under different scenarios.